2002
DOI: 10.1006/mthe.2002.0654
|View full text |Cite
|
Sign up to set email alerts
|

BMP4-Expressing Muscle-Derived Stem Cells Differentiate into Osteogenic Lineage and Improve Bone Healing in Immunocompetent Mice

Abstract: Recent advances in molecular biology have led the way for novel approaches to improve bone healing. The ideal growth factor, vector, and delivery systems for producing bone in an immune competent animal model, however, have yet to be identified. Using a retrovirus encoding BMP4 and recently isolated muscle-derived stem cells (MDSCs), we demonstrated the following: MDSCs undergo osteogenic differentiation in response to BMP4 in a dose-dependent manner; retrovirus encoding BMP4 can efficiently transduce MDSCs, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 30 publications
3
123
0
3
Order By: Relevance
“…16,19 Furthermore, they can undergo multilineage differentiation toward skeletal muscle, bone, cartilage, and neural, endothelial, and hematopoietic tissues. 15,16,[20][21][22][23][24][25][26] They are found in murine skeletal muscle at a ratio of 1 in 100,000 cells, 16 a ratio similar to that of adult mesenchymal stem cells (MSCs) isolated from bone marrow aspirates. 5 Although this suggests that a large muscle biopsy will be required to isolate sufficient cells for therapeutic applications, this limitation is overcome by the fact that MDSCs and other stem cells are easily expanded in vitro without loss of progenitor characteristics.…”
Section: Stem Cells In Regenerative Medicine Current Progress With Mumentioning
confidence: 99%
See 1 more Smart Citation
“…16,19 Furthermore, they can undergo multilineage differentiation toward skeletal muscle, bone, cartilage, and neural, endothelial, and hematopoietic tissues. 15,16,[20][21][22][23][24][25][26] They are found in murine skeletal muscle at a ratio of 1 in 100,000 cells, 16 a ratio similar to that of adult mesenchymal stem cells (MSCs) isolated from bone marrow aspirates. 5 Although this suggests that a large muscle biopsy will be required to isolate sufficient cells for therapeutic applications, this limitation is overcome by the fact that MDSCs and other stem cells are easily expanded in vitro without loss of progenitor characteristics.…”
Section: Stem Cells In Regenerative Medicine Current Progress With Mumentioning
confidence: 99%
“…21 MDSCs have also led to bone formation and healed critical-sized calvarial and long bone defects when genetically engineered to express BMP2 or BMP4. 15,[22][23][24][25][26] They were found within the newly formed bone and some co-localized with osteocalcin, suggesting that the cells differentiated into osteogenic cells. 15 …”
Section: Stem Cells In Regenerative Medicine Current Progress With Mumentioning
confidence: 99%
“…1,2 A growing literature describes the responsiveness of bone to transfer of osteogenic cDNAs encoding bone morphogenetic proteins (BMPs) -2, -4, -6, -7 and -9. [3][4][5][6][7][8][9] The properties of those BMPs have many potential clinical applications, such as to accelerate the healing of fractures, improve the repair of non-unions and segmental defects, enhance spinal fusion and provide better fixation for prosthetic implants.…”
Section: Introductionmentioning
confidence: 99%
“…MDSCs could potentially be a novel cell source for cartilage tissue engineering. They are known to have multilineage differentiation potential, including the ability to differentiate into skeletal muscle, bone, neural, endothelial, and hematopoietic tissue (12,(18)(19)(20)(21)(22)(23). We have previously shown that muscle-derived cells, including MDSCs, can undergo chondrogenesis in vivo and in vitro (24,25).…”
mentioning
confidence: 99%